Effect of DLBS3233, Metformin, and Their Combination on the Expressions of VEGF and Endometriosis Implants in Endometriosis Mice (A Mouse Model in Endometriosis Study) - Wardana, Setya Girindra; Trisetiyono, Yuli; Hadijono, Raden Soerjo; Mulyantoro, Inu; Cahyanti, Ratnasari Dwi; Dewantiningrum, Julian (Diponegoro International Medical Journal, 2023)
Abstract Background: Endometriosis is a gynaecological disorder characterized by the presence of endometrial tissue outside the uterine cavity. The process of angiogenesis is regulated by VEGF which plays an important role in the development of endometriosis implants. Metformin is an insulin sensitizer that is known to have a beneficial effect in the treatment of endometriosis and DLBS3233 is a PPARγ agonist, it is hoped that it can reduce VEGF and reduce endometrial implants..Objective: To explore the effect of DLBS3233, metformin, and combination on VEGF expression and endometrial implant area of endometriosis-induced mice.Methods: This experimental study used 3-months old 28 BALB/c mice of endometriosis that were randomly and equally divided into four groups (K, P1, P2, and P3). On the 15th day, the K group was given a placebo, the P1 group was given DLBS3233 0.25 mg/day for 14 days, the P2 group was given metformin 4 mg/day for 14 days and the P3 group was given a combination. The immunohistochemistry of VEGF expression was performed from the abdominal cavity and pelvic peritoneal tissues of the mice and measured by the Remmele Scale Index, while the extracted mice's endometrial implants were analyzed with a computer tracing method. All data normality tests were calculated with the Shapiro-Wilk test. The mean difference test of all groups was analyzed using the one-way ANOVA test and the Kruskal-Wallis test.Results: There were significant differences in the expressions of VEGF (p=0.005) and endometrial implants (p=0.001). Expression of VEGF in the P3 group was significantly lower compared to others and endometrial implant area in the P2 group was significantly lower compared to others.Conclusion: DLBS3233 and Metformin may be a potentially effective drug treatments for endometriosis by decreasing VEGF expression and endometrial implants. Keywords: DLBS3233, Endometriosis, Metformin, VEGF